Vizită în Infern (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Alina-Mihaela Bizdadea explores the "domestic life" of the Underworld by comparing Margaret Atwood’s The Penelopiad with Homer’s Odyssey. The study maps an infernal space where light persists despite "burnt-out bulbs" and silence reigns. Using Andrei Oișteanu’s research, the author explains how rituals and narcotics facilitate entry into this realm. Through Penelope’s perspective, Hell is revealed as a timeless, monotonous place of mental reflection, where spirits exist without bodies, eternally nourished by asphodels. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.